Cadet Experience in Learning English for Specific Purposes (ESP) Through Teaching Factory and Micro Internship - Wibowo, Amiruddin Hadi; Oktavia, Wahyuni; Amrullah, Romanda Annas; Onivehu, Adams Ogirima; Muharlisiani, Lusy Tunik (Journal of English Education Program, 2025)
In the global maritime industry, English proficiency is essential for cadets to perform effectively in international settings. However, English for Specific Purposes (ESP) instruction in maritime education often lacks contextual application. This study explores how the integration of Teaching Factory (TEFA) and micro internships influences cadets"™ learning experiences in ESP programs. Drawing on a qualitative case study using narrative inquiry, this research involved 40 cadets from a maritime academy in Surabaya who had completed both micro internship programs. Data was collected through semi-structured interviews, questionnaires, and observations over six weeks, and analyzed thematically. Thematic analysis was employed to identify, analyze, and report patterns (themes) within the data. The Findings of this study showed that TEFA and micro internships provided real-world learning environments where cadets could apply ESP in authentic maritime contexts. Most cadets agreed that the ESP content was relevant to their future work and that these practical experiences improved their confidence and language use. TEFA helped cadets understand industrial communication, while micro internships offered direct exposure to professional situations, enhancing their ability to use English for technical and emergency communication. Additionally, cadets appreciated the industry-based guidance provided by ESP instructors. The study concludes that integrating work-based learning models like TEFA and micro internships with ESP instruction enhances cadets' linguisticompetence, motivation, and job readiness. These findings highlight the need for ESP curricula to be closely aligned with industry demands and call for stronger collaboration between educational institutions and maritime industries. This research contributes to the ongoing development of contextualized and applicable ESP programs in maritime education.